The Impact of Community Violence and an Organization's Procedural Justice Climate on Workplace Aggression - Dietz, Joerg; Robinson, Sandra L.; Folger, Robert; Baron, Robert A.; Schulz, Martín (Academy of Management Journal, 2003)
This study contrasts community violence and an organization's procedural justice climate (or lack thereof) as explanations for employee-instigated workplace aggression in the geographically dispersed plants of a nationwide organization. The findings showed that violent crime rates in the community where a plant resided predicted workplace aggression in that plant, whereas the plant's procedural justice climate did not.